Excessive consumption of green tea and its effect on kidney tissue in rabbits - Almuoswi, Hadeel Jabar Neama (International Journal of Psychosocial Rehabilitation, 2020)
Design this study for detection effect of Excessive green tea on kidney´s rabbet . Ten local rabbets were used after one month of dosage . a treatment group(6 rabbit) that is orally injected with green tea (20 ml) / gm. Daily(Four times a day) for one month . histological study was an accomplished for kidney . histological toxic was very clear in our sample by effect on renal tubular of thickness of bowman capsule and The removal of epithelial cells in the renal tubes and the accumulation of inflammatory cells, which showed vascular degeneration, was also observed.